Women and Development: Women's Struggle for Labour Participation in Banten - Ramadhan, Gilang; Nurrohman, Bayu (Prodi Ilmu Pemerintahan, Universitas AMIKOM Yogyakarta, 2023)
This research tries to elaborate on the dynamics that are happening to women and development in Banten province. With very basic issues for women including gender-biased social construction, social welfare and the gender movement in an effort to encourage the role of women in work participation in Banten. Women in Banten are still trapped in poverty due to the low gender gap index which affects the level of participation of the female labor force (TPAK), this is exacerbated by the lack of women's participation in women's organizations formed to empower women and encourage policies that can encourage women in work participation. The women's movement in promoting gender justice is divided into two aspects, namely empowering women through organizations and involving women in policy formulation, especially those related to gender equality in the field of work.